The large-m limit, and spin liquid correlations in kagome-like spin models - Yavors'kii, T. (Condensed Matter Physics, 2017)
It is noted that the pair correlation matrix χˆ of the nearest neighbor Ising model on periodic three-dimensional (d = 3) kagome-like lattices of corner-sharing triangles can be calculated partially exactly. Specifically, a macroscopic number 1/3N + 1 out of N eigenvalues of χˆ are degenerate at all temperatures T , and correspond to an eigenspace L− of χˆ, independent of T . Degeneracy of the eigenvalues, and L− are an exact result for a complex d = 3 statistical physical model. It is further noted that the eigenvalue degeneracy describing the same L− is exact at all T in an infinite spin dimensionality m limit of the isotropic m-vector approximation to the Ising models. A peculiar match of the opposite m = 1 and m → ∞ limits can be interpreted that the m → ∞ considerations are exact for m = 1. It is not clear whether the match is coincidental. It is then speculated that the exact eigenvalues degeneracy in L− in the opposite limits of m can imply their quasi-degeneracy for intermediate 1 É m < ∞. For an anti-ferromagnetic nearest neighbor coupling, that renders kagome-like models highly geometrically frustrated, these are spin states largely from L− that for m Ê 2 contribute to χˆ at low T . The m → ∞ formulae can be thus quantitatively correct in description of χˆ and clarifying the role of perturbations in kagome-like systems deep in the collective paramagnetic regime. An exception may be an interval of T , where the order-by-disorder mechanisms select sub-manifolds of L−. Зауважено, що парнокореляцiйну матрицю χˆ моделi Iзинґа найближчих сусiдiв на перiодичних тривимiрних (d = 3) каґомеподiбних гратках можна обчислити частково точно. Зокрема, 1/3N +1 iз N власних значень χˆ виродженi при усiх температурах T та вiдповiдають власному лiнiйному простору L− матрицi χˆ, незалежному вiд T . Виродження власних значень та L− — приклад точного результату для складної d = 3 моделi статистичної фiзики. Зауважено далi, що виродження власних значень, якi описують той самий L−, — точне при усiх T у границi безмежної вимiрностi спiна m, яку можна розглядати як наближення iзотропної m-векторної моделi до моделi Iзинґа. Своєрiдне спiвпадiння протилежних m = 1 та m → ∞ границь можна проiнтерпретувати у спосiб, що мiркування для m → ∞ залишаються точними при m = 1. Незрозумiло, чи спiвпадiння випадкове. Накiнець зроблено припущення, що точне виродження власних значень у L− у протилежних границях m = 1 та m → ∞ може означати їх квазiвиродження при 1 É m < ∞. Для антиферомагнiтної константи зв’язку мiж найближчими сусiдами, при якiй каґомеподiбнi моделi стають сильно геометрично фрустрованими, саме стани iз L− роблять переважний внесок у χˆ при низькiй T для m Ê 2. Це означає, що рiвняння у границi m → ∞ можуть бути чисельно правильнi для опису χˆ та уточнення ролi збурень у каґомеподiбних системах глибоко у режимi колективного парамаґнетика. Винятком може бути iнтервал T , де механiзми лад-безлад вибирають пiдпростори L−.